THE CHILD’S DENTAL TREATMENT WITH SEDATION: REASONS, DENTAL TREATMENT NEEDS, MEDICAL CONDITION, AND HISTORY OF DENTAL ANXIETY AMONG CHILDREN IN YARSI DENTAL HOSPITAL - Mia Mariani; Adang Bachtiar (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: The prevention and treatment of oral diseases in childhood and adolescence as the basis for good oral health throughout life is the aim of pediatric dentistry. The ability to care for the segment of the pediatric patients with fear and anxiety of dental treatment also with the medically compromised condition has become an important component of dental practice. Therefore, a need does exist for sedation services within the dentistry field. This study aimed to determine the reasons, dental treatment needs, medical condition, and history of dental anxiety in the analyzed group of pediatric patients.Methods: This was a cross-sectional study using secondary data from medical records data conducted by YARSI Dental Hospital from March to April 2019. About 30 data were eligible for this analysis. The dependent variable in this study was dental treatment with sedation. Independent variables consisted of reasons, dental treatment needs, medical condition, and history of dental anxiety. The data were analyzed using univariate and bivariate analysis.Results: In this study, there were 21 children (70%) doing dental treatment with sedation because of the need for dental treatment and intervention reason. There was a statistically significant interaction between reason and dental treatment with sedation with p-value = 0.023 < 0.05. Another finding, children with a history of dental anxiety were more likely to use dental treatment with sedation (43.3%). With p-value 0.935 > 0.05 there was no statistically significant interaction between the history of dental anxiety with dental treatment with sedation. This study also did not reveal a statistically significant correlation between the following variables: dental treatment needs (p=0.128) as well as children’s medical condition (p=0,091). Conclusions: Most of the correspondents were non-medically compromised children with a history of dental anxiety. The reasons they came to YARSI dental hospital were because of the need for dental treatment and intervention reason. Conservation was the most needed dental treatment. Of the 4 (four) variables studied, the highest influence was the relationship between reason with dental treatment with sedation.